AUGMENTED REALITY MUSHAF: MENGHIDUPKAN KEMBALI SENI TAFSIR VISUAL - Muhammad Syauqi (Yayasan An-Nur Meunara Baro, 2025)
This article explores the potential of the Augmented Reality Mushaf (AR Mushaf) as a contemporary medium to revitalize the visual exegesis of the Qur'an, a tradition that has diminished in the face of modernization. The study adopts a development research approach, involving interdisciplinary collaboration among Qur'anic scholars, calligraphers, and AR developers. A prototype of the AR Mushaf was developed and tested with three user groups—traditional Islamic boarding school students, Muslim university students, and converts to evaluate user responses regarding the reading experience and understanding of Qur'anic verses. The findings reveal that AR enables thematic exegesis through infographic animations, vocabulary clarification via augmented notes, and three-dimensional visualization of Qur'anic narratives. Approximately 78% of participants reported improved contextual comprehension of verses, and 62% felt a deeper reading experience, though 15% expressed concern about distraction from the sacred text. The discussion highlights the continuity between classical manuscript illumination and modern visual technology as a renewed form of Islamic artistic heritage. Additionally, the article addresses ethical and pedagogical considerations in the development of religious technologies, particularly the limits of sacred visualization and developers’ responsibilities in preserving Qur'anic integrity. The study concludes that AR Mushaf offers a promising bridge between tradition and innovation, provided it is guided by culturally and theologically sensitive development frameworks.